eningkatan Kompetensi Bidang Akuntansi Bagi Guru SMK yang Tergabung Dalam MGMP Akuntansi Kota Cimahi - Yeti Apriliawati; Arry Irawan; Sugih Sutrisno Putra; Setiawan . (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2022)
The quality of teachers in vocational education has an important role in producing graduates who are competitive in the industry. In fact, there are still many Vocational High School (SMK) teachers who do not yet have expertise competency certificates. This is one of the reasons for the high unemployment rate in Indonesia, which is dominated by SMK graduates at 10.42 percent in August 2019. According to the head of the Accounting Subject Teacher Board (MGMP) in the Cimahi, 21 accounting teachers members of the MGMP do not have a competency certificate. Based on these problems, we held training activities to add insight for vocational teachers regarding competency certification for accounting teachers in vocational schools in accordance with the competency certification scheme, and improve practical teaching skills through practicum modules that are in accordance with industrial conditions. The implementation of the PKM program begins with compiling training materials, conducting online pre-tests, evaluating pre-test results, training 5 competency units online, conducting face-to-face competency test simulations, providing simulation scoring results, and providing feedback regarding scoring results. From the results of this activity, the teachers who were treated showed high enthusiasm and were able to receive the training material well with indicators of post test results that were better than the pre test.Keywords: Competency Certification; Vocational high School; Accounting Competence